Endothelial glycocalyx thickness and platelet-vessel wall interactions during atherogenesis - Reitsma, Sietze; oude Egbrink, Mirjam G. A.; Heijnen, Viviane V. Th.; Megens, Remco T. A.; Engels, Wim; Vink, Hans; W. Slaaf, Dick; van Zandvoort, Marc A. M. J. (Thrombosis and Haemostasis, 2011)
The endothelial glycocalyx (EG), the luminal cover of endothelial cells, is considered to be atheroprotective. During atherogenesis, platelets adhere to the vessel wall, possibly triggered by simultaneous EG modulation. It was the objective of this study to investigate both EG thickness and platelet-vessel wall interactions during atherogenesis in the same experimental model. Intravital fluorescence microscopy was used to study platelet-vessel wall interactions in vivo in common carotid arteries and bifurcations of C57bl6/J (B6) and apolipoprotein E knock-out (ApoE-/-) mice (age 7 – 31 weeks). At the same locations, EG thickness was determined ex vivo using two-photon laser scanning microscopy. In ApoE-/- bifurcations the overall median level of adhesion was 48 platelets/mm2 (interquartile range: 16 – 80), which was significantly higher than in B6 bifurcations (0 (0 – 16), p = 0.001). This difference appeared to result from a significant age-dependent increase in ApoE-/- mice, while no such change was observed in B6 mice. At the same time, the EG in ApoE-/- bifurcations was significantly thinner than in B6 bifurcations (2.2 vs. 2.5 μm, respectively; p < 0.05). This resulted from the fact that in B6 bifurcations EG thickness increased with age (from 2.4 μm in young mice to 3.0 μm in aged ones), while in bifurcations of ApoE-/- mice this growth appeared to be absent (2.2 μm at all ages). During atherogenesis, platelet adhesion to the wall of the carotid artery bifurcation increases significantly. At the same location, EG growth with age is hampered. Therefore, glycocalyx-reinforcing strategies could possibly ameliorate atherosclerosis.
Keywords: Atherogenesis; carotid artery; endothelial glycocalyx; platelets; mice